Antigenic and cryo-electron microscopy structure analysis of a chimeric sapovirus capsid - Miyazaki, Naoyuki; Hansman, Grant S. (Journal of virology, 2016)
ABSTRACT The capsid protein (VP1) of all caliciviruses forms an icosahedral particle with two principal domains, shell (S) and protruding (P) domains, which are connected via a flexible hinge region. The S domain forms a scaffold surrounding the nucleic acid, while the P domains form a homodimer that interacts with receptors. The P domain is further subdivided into two subdomains, termed P1 and P2. The P2 subdomain is likely an insertion in the P1 subdomain; consequently, the P domain is divided into the P1-1, P2, and P1-2 subdomains. In order to investigate capsid antigenicity, N-terminal (N-term)/S/P1-1 and P2/P1-2 were switched between two sapovirus genotypes GI.1 and GI.5. The chimeric VP1 constructs were expressed in insect cells and were shown to self-assemble into virus-like particles (VLPs) morphologically similar to the parental VLPs. Interestingly, the chimeric VLPs had higher levels of cross-reactivities to heterogeneous antisera than the parental VLPs. In order to better understand the antigenicity from a structural perspective, we determined an intermediate-resolution (8.5-Å) cryo-electron microscopy (cryo-EM) structure of a chimeric VLP and developed a VP1 homology model. The cryo-EM structure revealed that the P domain dimers were raised slightly (∼5 Å) above the S domain. The VP1 homology model allowed us predict the S domain (67-229) and P1-1 (229-280), P2 (281-447), and P1-2 (448-567) subdomains. Our results suggested that the raised P dimers might expose immunoreactive S/P1-1 subdomain epitopes. Consequently, the higher levels of cross-reactivities with the chimeric VLPs resulted from a combination of GI.1 and GI.5 epitopes. IMPORTANCE We developed sapovirus chimeric VP1 constructs and produced the chimeric VLPs in insect cells. We found that both chimeric VLPs had a higher level of cross-reactivity against heterogeneous VLP antisera than the parental VLPs. The cryo-EM structure of one chimeric VLP (Yokote/Mc114) was solved to 8.5-Å resolution. A homology model of the VP1 indicated for the first time the putative S and P (P1-1, P2, and P1-2) domains. The overall structure of Yokote/Mc114 contained features common among other caliciviruses. We showed that the P2 subdomain was mainly involved in the homodimeric interface, whereas a large gap between the P1 subdomains had fewer interactions.
Accepted manuscript posted online 23 December 2015
Gesehen am 08.06.2020